A method for gamma irradiation preparation of hollow tubular graphitic phase carbon nitride / platinum nanoparticle composite

CN113506883BActive Publication Date: 2026-10-30TIANJIN POLYTECHNIC UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110478902.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2026-10-30
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

但是燃料电池的发展存在以下问题:(1)阴极氧还原反应动力学缓慢严重制约燃料电池发展速度;(2)目前商业阴极氧还原催化剂不仅价格昂贵,而且多为化学合成,污染环境,不利于生态友好

Benefits of technology

[0017]1.本发明中制备中空管状石墨相氮化碳/PtNPs复合材料使用绿色无污染的伽马辐照技术,反应温和,无副产物生成;操作简单、易于控制,重复性好,有利于工业化的大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113506883B_ABST
    Figure CN113506883B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of electrocatalytic oxygen reduction material preparation, and particularly relates to a preparation method of a tubular graphite phase carbon nitride oxygen reduction catalyst. The present application first prepares graphite phase carbon nitride nanosheets based on a ball milling method, which can significantly reduce the particle size of the material and increase the specific surface area. Gamma irradiation modification of the material can accelerate the rapid migration of electrons on the surface of carbon nitride, effectively improve the conductivity of graphite phase carbon nitride, and make the oxygen reduction reaction proceed efficiently. At the same time, gamma irradiation can effectively increase the active sites on the surface of carbon nitride material, promote the improvement of oxygen reduction activity, and this preparation method is simple, convenient, environmentally friendly and pollution-free, and can be mass-produced and has universality. The tubular graphite phase carbon nitride catalyst prepared by the gamma irradiation method has a small Tafel slope in the oxygen reduction reaction process, a fast four-electron transfer path, and a performance far superior to commercial platinum carbon and graphite phase carbon nitride-based electrodes reported in existing literature, which can provide a reference for the structural design of future energy catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic material preparation technology, and in particular relates to a method for preparing a tubular graphite phase carbon nitride oxygen reduction electrocatalytic material. Background Technology

[0002] Currently, due to global warming and energy depletion, people are committed to developing various new energy sources. Fuel cells have attracted attention due to their environmental friendliness and low energy consumption. However, the development of fuel cells faces the following problems: (1) the slow kinetics of the cathode oxygen reduction reaction seriously restricts the development speed of fuel cells; (2) currently available commercial cathode oxygen reduction catalysts are not only expensive, but also mostly chemically synthesized, polluting the environment and being detrimental to eco-friendliness. Therefore, it is urgent to prepare cost-effective and high-performance oxygen reduction electrocatalysts using environmentally friendly and green synthesis methods.

[0003] Graphitic carbon nitride (g-C3N4) has attracted widespread attention in the field of energy catalysis due to its abundant sources, excellent stability, low cost, and nitrogen-rich six-membered ring structure. The structure of g-C3N4 is similar to graphene, but unlike graphene, it is also rich in nitrogen, providing uniform and abundant active sites. Furthermore, the planar structure of g-C3N4 exhibits significant structural defects, which can increase oxygen adsorption, resulting in good activity in catalytic applications. Therefore, we propose using this inexpensive and easily fabricated two-dimensional sheet material, graphitic carbon nitride (g-C3N4), in the field of electrocatalysts to minimize costs. The layers of carbon nitride are connected by hydrogen bonds, exhibiting a graphite stacked structure. This results in poor conductivity and a small specific surface area, thus limiting its application in electrocatalysis. Based on this, researchers have found that morphology control and elemental doping can significantly improve the electrocatalytic performance of carbon nitride. Meanwhile, gamma-ray irradiation, due to its high energy, strong penetrability, fast speed, environmental friendliness, and the fact that it is usually carried out at room temperature in most applications, has begun to be used as a clean and simple synthetic method to modify the nanostructure and properties of carbon materials and promote their surface grafting modification.

[0004] Based on the above research, this patent utilizes the inherent stability and good conductivity of carbon materials to form conjugated carbon materials with graphitic carbon nitride, significantly improving the electron mobility of the material. Simultaneously, we introduce environmentally friendly gamma irradiation technology to prepare carbon nitride-based oxygen reduction electrocatalysts supported on noble metals, eliminating the need for other toxic reagents and demonstrating environmental friendliness. Furthermore, introducing noble metal elements into the interlayer of carbon nitride allows for the introduction of a large number of free electrons into the g-C3N4 semiconductor, greatly improving the charge transport capability of the original g-C3N4. The pure g-C3N4 molecule contains sites composed of six equivalent N atoms with lone pairs of electrons; these sites readily form chemical bonds with metal ions, reducing the metal ion deposition rate while simultaneously increasing the electron conduction rate. Additionally, tubular carbon nitride was prepared using structural engineering, exhibiting a large specific surface area and excellent stability in electrocatalytic performance testing.

[0005] Chinese Patent CN105236364A discloses a method for preparing tubular carbon nitride using natural rod-shaped silicate clay as a template. However, this method requires the removal of the template with highly toxic hydrogen fluoride and ammonium bifluoride, polluting the environment and posing a health hazard. Chinese Patent CN109603880B discloses a method for preparing hollow tubular carbon nitride photocatalytic materials, but the prepared materials exhibit uneven distribution of tubular structures, resulting in poor practical application performance. Chinese Patent CN109772418A discloses a phosphorus-doped tubular carbon nitride nanomaterial. The hydrothermal reaction method used in its preparation process results in low material yield, and the synthesized material has no pores or defects on its surface, leading to a limited number of active sites, which is detrimental to the efficient electrocatalytic oxygen reduction reaction. To overcome the shortcomings of existing tubular carbon nitride synthesis technologies, this patent utilizes gamma irradiation technology. The preparation process does not require toxic reagents, making it environmentally friendly and pollution-free. Furthermore, irradiation modification of the material introduces more active sites, further enhancing its catalytic performance. This patent describes the preparation of platinum- and carbon-co-doped g-C3N4 with a tubular structure as an electrocatalyst for ORR (Orthogonal Reduction). Platinum doping can narrow the band gap of g-C3N4, promote electron transfer, and increase the number of active sites. Furthermore, the tubular carbon nitride structure can promote O2 adsorption and transfer. The results show that the hollow tubular graphitic carbon nitride / platinum nanoparticle (PtNPs) composite material prepared by gamma irradiation exhibits enhanced ORR performance.

[0006] This invention prepares tubular g-C3N4 by doping a carbon skeleton and platinum into the triazine ring structure of carbon nitride, thus overcoming the shortcomings of existing modification and design methods for graphitic carbon nitride in the field of electrocatalysis. This provides more options for catalyst synthesis and can offer some reference value for basic research on graphitic carbon nitride in the field of electrocatalysis. Summary of the Invention

[0007] This invention addresses the problem that the low electrical conductivity of graphitic carbon nitride restricts its development in the field of electrocatalysis. It provides a method for preparing a tubular graphitic carbon nitride high-efficiency oxygen reduction catalyst. By doping with metal elements, the electronic structure of the carbon nitride surface is regulated to accelerate electron migration. At the same time, the tubular oxygen reduction electrocatalytic material is prepared, which allows oxygen to be rapidly adsorbed and desorbed on the material surface, which is beneficial to the catalytic mass transfer process.

[0008] The technical solution of this invention provides a method for preparing platinum- and carbon-co-doped tubular carbon nitride, characterized by the following specific steps: (1) Take an appropriate amount of urea and sodium citrate and place them in a muffle furnace for high-temperature calcination to prepare graphitic carbon nitride; (2) Graphite phase carbon nitride and 5mm zirconium beads were ball-milled at a ball-to-material ratio of 1:20 to prepare graphite phase carbon nitride nanosheets. (3) After mixing graphitic carbon nitride and pyrrole monomers in a certain proportion and sonicating, they were placed in a container. 60 Carbon nitride was prepared under Co gamma ray irradiation under saturated nitrogen gas conditions;

[0009] After the reaction was completed, the sample was characterized structurally and its electrochemical performance was tested.

[0010] In this invention, the ratio of urea to sodium citrate is 10:1, and the calcination temperature is 500℃~800℃.

[0011] In this invention, the zirconium beads used in the ball milling process are 28 mm in size, and the ball milling time is 6 to 14 hours.

[0012] In this invention, carbonization is performed using a tube furnace, with the temperature set to 450°C to 900°C.

[0013] In this invention, the irradiation medium is nitrogen gas, the irradiation temperature is room temperature, and the irradiation dose is 90–200 kGy.

[0014] In this invention, the platinum precursor accounts for 5% to 15% wt of the graphitic carbon nitride.

[0015] The difference between this invention and common tubular material preparation methods is that common tubular material preparation methods usually require template methods, which involve etching the template with highly toxic strong acids, resulting in pollution and harm to the human body. However, this invention does not require the use of templates or highly toxic chemical reagents to remove the template, making it environmentally friendly, safe, and pollution-free.

[0016] The present invention has at least the following beneficial effects:

[0017] 1. The hollow tubular graphitic carbon nitride / PtNPs composite material prepared in this invention uses green and pollution-free gamma irradiation technology. The reaction is mild and no by-products are generated. The operation is simple, easy to control, and has good repeatability, which is conducive to large-scale industrial production.

[0018] 2. This invention uses ball milling to prepare carbon nitride nanosheets, then introduces carbon materials and the noble metal platinum to enhance the conductivity and catalytic activity of carbon nitride. The resulting material possesses a regular tubular structure, and successfully prepares tubular carbon nitride materials conjugated with crystalline carbon, optimizing the specific surface area and charge transport capacity of carbon nitride and enhancing its oxygen reduction activity. This method requires no templates or toxic reagents.

[0019] 3. The tubular carbon nitride prepared in this invention is formed by the rolling and overlapping of carbon nitride sheets, with a diameter of 1-2 μm and a length greater than 2 μm. It possesses a large specific surface area, significant catalytic activity, and a continuous electron transport pathway. The tubular carbon nitride material prepared in this invention can achieve an oxygen reduction CV reduction peak potential of 0.795 V and a limiting current density of 6.9 mA cm⁻¹. -2 It exhibits high four-electron selectivity; rapid reaction kinetics and low Tafel slope; and stable tubular structure, with a more stable current than commercial platinum-carbon materials after 5000 s of cycling.

[0020] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0021] Figure 1 (a) and (b) are transmission electron microscopy (TEM) images of the original graphitic carbon nitride and the hollow tubular graphitic carbon nitride / PtNPs composite material prepared in Example 1, respectively.

[0022] Figure 2 X-ray diffraction (XRD) patterns of untreated graphitic carbon nitride and hollow tubular graphitic carbon nitride / PtNPs composites prepared in Examples 1-3;

[0023] Figure 3 X-ray diffraction (XPS) patterns of untreated graphitic carbon nitride and hollow tubular graphitic carbon nitride / PtNPs composites prepared in Examples 1-3;

[0024] Figure 4 (a) Electrochemical cyclic voltammetry (CV) curves and (b) electrochemical linear sweep voltammetry (LSV) curves of untreated graphitic carbon nitride and hollow tubular graphitic carbon nitride / PtNPs composite samples prepared in Examples 1-3.

[0025] Figure 5 A comparison of the average number of transferred electrons for untreated graphitic carbon nitride and hollow tubular graphitic carbon nitride / PtNPs composites prepared in Example 1, and commercial Pt / C.

[0026] Figure 6A comparison of the Tafel curve slopes of untreated graphitic carbon nitride, hollow tubular graphitic carbon nitride / PtNPs composites prepared in Example 1, and commercial Pt / C.

[0027] Figure 7 Comparison of the cycling stability of the hollow tubular graphitic carbon nitride / PtNPs composite material prepared for Example 1 and commercial Pt / C in the oxygen reduction catalytic reaction; Detailed Implementation

[0028] The following detailed description, with reference to specific embodiments, provides a method for preparing hollow tubular graphitic carbon nitride / PtNPs composite materials using gamma irradiation, as provided by this invention. It should be understood that the specific examples are for illustrative purposes only and do not limit the scope of application of this invention. Any modifications and variations made to this invention that do not depart from its purpose and scope fall within the protection scope of this invention.

[0029] The schemes of Examples 1-3 are as follows: Table 1. Graphite-phase carbon nitride structural design parameters for Examples 1-3

[0030] Example 1:

[0031] Step 1: Put a certain proportion of urea and citric acid into a crucible, stir evenly, place it in a muffle furnace, heat it to 550°C at a rate of 2°C / min in an air atmosphere, hold it at that temperature for 2 hours, and take out the sample after it cools naturally. This is bulk graphitic carbon nitride.

[0032] The second step involves using a planetary ball mill to grind bulk graphitic carbon nitride into powder. The ball milling speed is 640 rpm, the ball milling time is 10 hours, and the zircon bead size is 5 nm. Then, the ball-milled sample is sieved through a 500-mesh sieve to obtain small-sized graphitic carbon nitride nanosheets with smaller and more uniform particle sizes.

[0033] Step 3: Weigh 100 mg of the graphitic carbon nitride prepared in step 2, add 184 μL of phytic acid, 1104 μL of pyrrole, and 1 mL of isopropanol mixed solution to it, then add the pre-prepared ammonium persulfate solution dropwise, and sonicate for 10 min. Then wash three times with deionized water by centrifugation and dry in a vacuum oven.

[0034] Step 4: Place the dried sample in a ceramic boat and heat it to 700°C in a high-temperature tube furnace under an inert atmosphere at a heating rate of 5°C / min. Then, hold the temperature for 2 hours to obtain carbon nitride graphite phase doped with carbon.

[0035] Step 5: Mix carbon-doped graphitic carbon nitride with an aqueous solution of chloroplatinic acid, setting the platinum loading to 10 wt%. Purge the solution with nitrogen saturation gas for 30 minutes to remove oxygen. Then place the mixture in a container... 60 A carbon-doped tubular graphitic carbon nitride material loaded with noble metal platinum can be obtained by using a Co-γ-ray irradiation source (absorbed dose rate of 2.7 kGy / h) and an irradiation dose of 140 kGy, followed by centrifugal cleaning and freeze drying.

[0036] Step 6: Disperse the obtained carbon-doped platinum-supported tubular graphite phase carbon nitride material in Nafion's ethanol solution, and prepare a uniformly dispersed catalyst ink by ultrasonication. Drop the uniformly dispersed catalyst ink onto a clean glassy carbon electrode, let it air dry, and then perform electrochemical performance testing.

[0037] Example 2:

[0038] The first step is to put a certain proportion of urea and citric acid into a crucible, stir it evenly, place it in a muffle furnace, and heat it to 550°C at a rate of 2.5°C / min in an air atmosphere, hold it at that temperature for 3 hours, and take the sample out after it cools down naturally. This is the bulk graphitic carbon nitride.

[0039] The second step is to use a planetary ball mill to grind the bulk graphitic carbon nitride into powder. The ball milling speed is 240 rpm and the ball milling time is 8 hours. The zircon bead size is 3 nm. Then, the ball-milled sample is sieved through a 500-mesh sieve to obtain small-sized graphitic carbon nitride with smaller and more uniform particle size.

[0040] Step 3: Weigh 100 mg of small-sized graphitic carbon nitride, add 184 μL of phytic acid, 1104 μL of pyrrole, and 1 mL of isopropanol mixed solution, then add the pre-prepared ammonium persulfate solution dropwise, and sonicate for 10 min. Next, wash three times with deionized water by centrifugation and dry in a vacuum oven.

[0041] Step 4: Place the dried sample in a ceramic boat and heat it to 600°C in a high-temperature tube furnace under an inert atmosphere at a heating rate of 3°C / min. Then, hold the temperature for 2 hours to obtain carbon-doped graphitic carbon nitride.

[0042] Step 5: Mix carbon-doped tubular graphitic carbon nitride with an aqueous solution of chloroplatinic acid, purge with nitrogen saturated gas for 30 minutes to remove oxygen from the solution, and then place... 60 Carbon-doped platinum-loaded tubular graphitic carbon nitride material can be obtained by using a Co-γ-ray irradiation source (absorbed dose rate of 0.3 kGy / h) and irradiation dose of 100 kGy, followed by centrifugal cleaning and freeze-drying.

[0043] Step 6: Disperse the obtained carbon-doped platinum-supported tubular graphite phase carbon nitride material in Nafion's ethanol solution, and prepare a uniformly dispersed catalyst ink by ultrasonication. Drop the uniformly dispersed catalyst ink onto a clean glassy carbon electrode, let it air dry, and then perform electrochemical performance testing.

[0044] Example 3:

[0045] Step 1: Put a certain proportion of urea and citric acid into a crucible, stir evenly, place it in a muffle furnace, heat it to 550°C at a rate of 3°C / min in an air atmosphere, hold it at that temperature for 1 hour, and take out the sample after it cools naturally. This is bulk graphitic carbon nitride.

[0046] The second step is to use a planetary ball mill to grind the bulk graphitic carbon nitride into powder. The ball milling speed is 360 rpm and the ball milling time is 12 hours. The zircon bead size is 6 nm. Then, the ball-milled sample is sieved through a 500-mesh sieve to obtain small-sized graphitic carbon nitride with smaller and more uniform particle size.

[0047] Step 3: Weigh 100 mg of small-sized graphitic carbon nitride, add 184 μL of phytic acid, 1104 μL of pyrrole, and 1 mL of isopropanol mixed solution, then add the pre-prepared ammonium persulfate solution dropwise, and sonicate for 10 min. Next, wash three times with deionized water by centrifugation and dry in a vacuum oven.

[0048] The fourth step is to place the dried sample in a ceramic boat and heat it to 800°C in a high-temperature tube furnace under an inert atmosphere at a heating rate of 2.5°C / min, and then hold it at that temperature for 2 hours to obtain carbon nitride with carbon-doped graphite phase.

[0049] Step 5: Mix carbon-doped tubular graphitic carbon nitride with an aqueous solution of chloroplatinic acid, purge with nitrogen saturated gas for 30 minutes to remove oxygen from the solution, and then place... 60 Carbon-doped platinum-loaded tubular graphitic carbon nitride material can be obtained by using a Co-γ-ray irradiation source (absorbed dose rate of 2.7 kGy / h) and irradiation dose of 180 kGy, followed by centrifugal cleaning and freeze-drying.

[0050] Step 6: Disperse the obtained carbon-doped platinum-supported tubular graphite phase carbon nitride material in Nafion's ethanol solution, and prepare a uniformly dispersed catalyst ink by ultrasonication. Drop the uniformly dispersed catalyst ink onto a clean glassy carbon electrode, let it air dry, and then perform electrochemical performance testing.

Claims

1. A method for preparing hollow tubular graphitic carbon nitride / platinum nanoparticle composite materials by gamma irradiation, characterized in that: The method includes the following steps: Step 1: Mix urea and sodium citrate in a 10:1 ratio and then pyrolyze at high temperature to prepare graphitic carbon nitride. Step 2: Ball mill the graphitic carbon nitride to prepare graphitic carbon nitride nanosheets; Step 3: Add graphitic carbon nitride nanosheets to a mixed solution of phytic acid, pyrrole, and isopropanol, then add ammonium persulfate solution dropwise, perform ultrasonic polymerization, then centrifuge, wash, and dry, and then perform high-temperature carbonization under an inert atmosphere to obtain carbon-doped graphitic carbon nitride. Step 4: Mix carbon-doped graphitic carbon nitride with an aqueous solution of chloroplatinic acid, then place the mixture in a brown bottle filled with an argon atmosphere. 60 In a Co gamma-ray source, the gamma-ray irradiation dose is 100–180 kGy, and the absorbed dose rate is 0.3–2.7 kGy / h. The solution is then centrifuged, washed, and freeze-dried to obtain irradiated modified tubular graphitic carbon nitride samples.

2. The method for preparing hollow tubular graphitic carbon nitride / platinum nanoparticle composite materials by gamma irradiation as described in claim 1, characterized in that: In step two, the preparation of graphitic carbon nitride nanosheets is carried out using a planetary ball mill with a rotation speed of 240 rpm to 640 rpm and a milling time of 8 to 12 hours. The zircon beads used in the milling process have a size of 3 to 6 nm.

3. The method for preparing hollow tubular graphitic carbon nitride / platinum nanoparticle composite materials by gamma irradiation as described in claim 1, characterized in that: In step three, the carbon-doped graphitic carbon nitride nanosheets are prepared by ultrasonic polymerization of carbon nitride and pyrrole followed by high-temperature pyrolysis. A quartz tube furnace is used for pyrolysis, with a heating rate of 2.5–5 °C / min, a temperature range of 500–800 °C, and a holding time of 1–3 h.

4. The method for preparing hollow tubular graphitic carbon nitride / platinum nanoparticle composite materials by gamma irradiation as described in claim 1, characterized in that: The platinum precursor accounts for 5% to 15% wt of the graphitic carbon nitride used.

Citation Information

Patent Citations

  • Preparation method of tubular carbon nitride

    CN105236364A

  • Hollow tubular carbon nitride photocatalysts, their preparation methods and applications

    CN109603880B

  • Phosphorus-doped tubular carbon nitride micro-nano material and application thereof in waste gas catalytic treatment

    CN109772418A

  • Metal / metal oxide / g-C3N4 composite photocatalytic material and preparation method thereof

    CN104888832A

  • Preparation method and application of carbon-nitride-based composite oxygen reduction electrocatalyst-modified disc electrode

    CN106992304A